Vaccine Literacy: A Concept Analysis - Avie Rotsen Badua; Krystelle Joy Caraquel; Marjorie Cruz; Roison Andro Narvaez (Humanistic Network for Science and Technology (HNST), 2022)
The 2019 Coronavirus Disease (COVID-19) is dubbed as one of the deadliest and worst global pandemics. Many pandemic policies and programs were implemented in different countries across the globe, including creating vaccines that would enhance human immunity against the symptoms caused by the virus. Since then, debates on vaccines have emerged, citing vaccine hesitancy often associated with certain factors like socioeconomic status, beliefs, and vaccine awareness. This birthed an intensive call for vaccine literacy as an effective means of encouraging people to get vaccinated against viruses. This paper uses the Walker and Avant (2019) approach of concept analysis with the help of its eight systematic stages. Results showed that vaccine literacy was adopted after the concept of health literacy. It is defined as a process of providing vaccine information, building communication, and increasing people's engagement about vaccines. The identified defining attributes of vaccine literacy include